Anaerobic digestion of food waste to volatile fatty acids and hydrogen at high organic loading rates in immersed membrane bioreactors. (June 2020) - Wainaina, Steven; Awasthi, Mukesh Kumar; Horváth, Ilona Sárvári; Taherzadeh, Mohammad J.
Abstract: The organic loading rate (OLR) is an essential parameter that controls the anaerobic digestion process. This work investigated the performance of immersed membrane bioreactors operated at high OLRs of 4, 6, 8 and 10 g volatile solids (VS)/L/d regarding the fermentation behavior, product recovery and microbial dynamics during the acidogenic fermentation of food waste to volatile fatty acids (VFAs) and hydrogen. The highest yield of 0.52 g VFA/gVSadded was attained at 6 g VS/L/d, while an optimal hydrogen yield of 14.7 NmL/gVSadded was obtained at 8 g VS/L/d. The bacterial populations, analyzed using 16S rRNA gene amplicon sequencing, consisted mainly of Firmicutes and Actinobacteria at OLRs 4 and 8 g VS/L/d while Firmicutes, Actinobacteria and Proteobacteria phyla dominated at 6 and 10 g VS/L/d. Moreover, the presence of Clostridium and Lactobacillus genera correlated with the acetate, butyrate, caproate and lactate production. Highlights: Production of VFAs and hydrogen in membrane bioreactors at high OLRs was assessed. The OLR of 6 g VS/L/d resulted in the highest yield of VFAs at 0.52 gVFA/gVSadded . The OLR of 8 g VS/L/d resulted in the highest yield of hydrogen at 14.7 NmL/gVSadded . Dominance of acetate, butyrate and caproate was due to the presence of Clostridium . Relative abundance of Lactobacillus influenced the biosynthesis of lactate.